The role of refugee and migrant migration status on medication adherence: Mediation through illness perceptions. - Wejdan Shahin; Gerard A Kennedy; Wendell Cockshaw; Ieva Stupans (PLoS ONE)
Background Illness perceptions may vary between different populations. This raises the question as to whether refugees and migrants of the same ethnic background have different perceptions. Understanding differences may have a significant impact on enhancing medication adherence in these groups. Objective The study examined the associations and differences between illness perceptions, and medication adherence in hypertensive Middle Eastern migrants and refugees. Methods Middle Eastern refugees and migrants (≥30 years old), with hypertension were recruited from Arabic community groups in Australia and asked to complete a cross-sectional survey. The survey consisted of basic socio-demographic and clinical profile, self-reported illness perceptions, and self-reported medication adherence. The outcome measure was the Medication Adherence Questionnaire. Simple mediation modelling was applied to examine the role of illness perceptions as a mediator between different migration statuses, and medication adherence. Results A total of 320 participants were recruited; 168 refugees, and 152 migrants. Educational level was found to be positively significantly associated with medication adherence in refugees, p = 0.003, while employed migrants were more likely to report higher adherence to hypertensive medication, p = 0.005. In both groups, there was a significant association between illness perceptions and medication adherence p = 0.0001. Significant differences were found between both groups regarding adherence and illness perceptions variables. Refugees had more negative illness perceptions and were less adherent than migrants. Illness perception was a mediator in the relationship between migration status and medication adherence; the unstandardized indirect effect was 0.24, and the 95% confidence interval ranged from (0.21-0.36). Conclusions To achieve better adherence to medications in vulnerable populations such as refugees, illness perceptions need to be understood, and differentiated from other populations, such as migrants from similar backgrounds. Patients' education about illnesses and medications should be specific and targeted to each population. Interventional studies are recommended to modify refugees' and migrants' illness perceptions, to enhance medication adherence and wellbeing.